2016
DOI: 10.1353/eca.2016.0005
|View full text |Cite
|
Sign up to set email alerts
|

Grasp the Large, Let Go of the Small: The Transformation of the State Sector in China

Abstract: In the late 1990s, China's industrial sector was dominated by state-owned firms. We document how this changed after 1998. More than 80 percent of the state-owned firms in 1998 were shut down or privatized by 2007. Among firms we classify as state-controlled in 2007, many were restructured and registered as private firms with a controlling share held by a stateowned conglomerate or were new firms established after 1998. In 2007, almost half of the state-controlled firms were registered as private firms, and abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(100 citation statements)
references
References 30 publications
8
81
0
Order By: Relevance
“…During the sample period China carried out dramatic reforms of the SOEs including privatising smaller firms, merging and corporatising larger ones, and creating new, large state-owned firms. The surviving state-owned and privatised firms show fast TFP growth (Hsieh and Song, 2015). Excluding these firms from our analysis mitigates any concern that industry-specific TFP improvements may be the result of within-firm efficiency gains due to the SOE reforms.…”
Section: The Influence Of the Soe Reformsmentioning
confidence: 99%
“…During the sample period China carried out dramatic reforms of the SOEs including privatising smaller firms, merging and corporatising larger ones, and creating new, large state-owned firms. The surviving state-owned and privatised firms show fast TFP growth (Hsieh and Song, 2015). Excluding these firms from our analysis mitigates any concern that industry-specific TFP improvements may be the result of within-firm efficiency gains due to the SOE reforms.…”
Section: The Influence Of the Soe Reformsmentioning
confidence: 99%
“…First, we study how the privatisation would have proceeded if the job protection measures had been in force in 1998. As stressed in numerous studies, privatisation is certainly a big part of the recent growth in China (Song et al ., ; Hsieh and Song, ; Li, ). Using a decomposition of growth rates, Deng et al .…”
Section: State‐controlled Plants: Privatisation and Policy Effectsmentioning
confidence: 99%
“…Capital is calculated by the book value of fixed asset net of depreciation. To control for industry effects, we follow Hsieh and Song () and use industry labour share to weight capital intensity (Cap./emp. ), value added per worker (Va./emp.…”
Section: Exportersmentioning
confidence: 99%
See 1 more Smart Citation
“…Research questions have addressed whether these SOEs are relatively inefficient and whether the transformation of SOEs has contributed to China's economic growth. According to Hsieh and Song (2015), the underlying principle of China's SOE reform can be described as "Grasp the large, let go of the small," which means that the government should privatize small SOEs but still control the large, important ones. However, they found that the privatization of SOEs from 1997 to 2008 accounted for only 3% of the aggregate growth in China's industrial output.…”
mentioning
confidence: 99%